Conjugate of PAMAM Dendrimer, Doxorubicin and Monoclonal Antibody—Trastuzumab: The New Approach of a Well-Known Strategy - Monika Marcinkowska (Polymers, 2018)
The strategy utilizing trastuzumab, a humanized monoclonal antibody against human epidermal growth receptor 2 (HER-2), as a therapeutic agent in HER-2 positive breast cancer therapy seems to have advantage over traditional chemotherapy, especially when given in combination with anticancer drugs. However, the effectiveness of single antibody or antibody conjugated with chemotherapeutics is still far from ideal. Antibody–dendrimer conjugates hold the potential to improve the targeting and release of active substance at the tumor site. In the present study, we developed and synthesized PAMAM dendrimer–trastuzumab conjugates carrying doxorubicin (dox) specifically to cells overexpressing HER-2. 1HNMR, FTIR and RP-HPLC were used to characterize the products and analyze their purity. Toxicity of PAMAM–trastuzumab and PAMAM–dox–trastuzumab conjugates compared with free trastuzumab and doxorubicin towards HER-2 positive (SKBR-3) and negative (MCF-7) human breast cancer cell lines was determined using MTT assay. Furthermore, the cellular uptake and cellular localization were studied by flow cytometry and confocal microscopy, respectively. A cytotoxicity profile of above mentioned compounds indicated that conjugate PAMAM–dox–trastuzumab was more effective when compared to free drug or the conjugate PAMAM–trastuzumab. Moreover, these results reveal that trastuzumab can be used as a targeting agent in PAMAM–dox–trastuzumab conjugate. Therefore PAMAM–dox–trastuzumab conjugate might be an interesting proposition which could lead to improvements in the effectiveness of drug delivery systems for tumors that overexpress HER-2.